Sustainable community-based tourism development for marginalised island communities in Kelantan: Evidence from Gugusan Kepulauan Tumpat. - Md Nasir, Syerina Azlin; Abu Bakar, Hatinah; Ismail , Nurazleena; Hajman, Firman (Journal of Islamic, Social, Economics and Development, 2026)
This study explores sustainable tourism development through a Community-Based Tourism (CBT) initiative in Gugusan Kepulauan Tumpat, Kelantan, with a focus on empowering marginalised island communities. Adopting an exploratory case study approach, the research employs interviews, focus group discussions, observations, and a questionnaire survey involving 29 community members across 10 islands. The study analyses existing community-based economic activities and identifies local tourism resources, which inform the development of a CBT clustering approach comprising three integrated categories: natural heritage, art and cultural heritage, and traditional food. The findings highlight the importance of active community participation, local ownership, and multi-stakeholder collaboration in structuring sustainable CBT initiatives. The proposed clustering framework offers a practical mechanism for enhancing value creation, diversifying livelihoods, and promoting inclusive tourism development, thereby contributing to community empowerment and long-term socio-economic resilience in marginalised island settings.